The Farmer Life School: experience from an innovative approach to HIV education among farmers in South Africa - Kees Swaans; Jacqueline Broerse; Monique Salomon; Maxwell Mudhara; Makhosazana Mweli; Joske Bunders (Taylor & Francis Group, 2008)
The Farmer Life School (FLS) is an innovative approach to integrating HIV education into life skills and technical training for farmers. This study aims to gain insight into the strengths and weaknesses of this relatively new approach, through the implementation of an adapted version in South Africa. The results are presented of a pilot with three groups of community gardeners, predominantly women, attending weekly sessions. Impact was assessed in terms of three key elements: participation, learning, and empowerment. Data were collected through extensive session reports, follow-up interviews, and reflection exercises with facilitators and participating groups and individuals. The results suggest that a group-based discovery learning approach such as the FLS has great potential to improve food security and wellbeing, while allowing participants to explore issues around HIV/AIDS. However, the analysis also shows that HIV/AIDS-related illness and death, and the factors that drive the epidemic and its impact, undermine farmers' ability to participate, the safety and trust required for learning, and the empowerment process. Participatory approaches such as the FLS require a thorough understanding of and adaptation to the context.